Formononetin and mizoribine inhibit Porcine Reproductive and Respiratory Syndrome Virus replication in vitro - Cui, Zhanding; Liu, Jinlong; Wang, Jinlong; Zhang, Jing; Cao, Yimei; Li, Kun; Zhao, Zhixun; Yuan, Hong; Bai, Xingwen; Ma, Xueqing; Li, Pinghua; Fu, Yuanfang; et al. (Frontiers in Nutrition, 2025)
This study delves into the antiviral efficacy of Formononetin (FMN) and Mizoribine (MZR) against the Porcine Reproductive and Respiratory Syndrome Virus (PRRSV), a virus with a considerable economic impact and a current void in effective treatments. FMN and MZR were found to inhibit various PRRSV strains in vitro, predominantly in the early stages of viral infection. Noteworthy was the observation of their synergistic effects when combined with Ribavirin. The study underscores the antiviral potential of FMN and MZR, particularly emphasizing their low cytotoxicity at specific concentrations. These results position FMN and MZR as promising antiviral agents against PRRSV, underscoring their low cytotoxicity and efficacy in early-stage viral inhibition. Such findings pave the way for their potential inclusion in future PRRSV management strategies.